APPLICATION OF THE HAVERSINE DISTANCE METHOD TO THE JOB AND VACANCIES SEARCH SYSTEM IN THE ENTERTAINMENT SECTOR IN INDONESIA - Edi Junaedi; Ariyanti, Fransisca Dini (Jurnal Teknik Informatika (Jutif), 2024)
The International Monetary Fund (IMF) projects that the poverty rate in Indonesia will reach 5.2% by 2024, ranking 59th in the world, Indonesia is the country in Southeast Asia with the highest poverty rate. The second highest poverty rate is in 2023. The percentage is projected to reach 5.3% this year. According to the Central Statistics Agency (BPS), in August 2023 the number of open unemployment in Indonesia will reach 7.86 million people, equivalent to 5.32% of the total national workforce. The Philippines will face the highest poverty rate in the region, followed by Indonesia next with a poverty rate of 5.4%. By 2023. this high poverty rate reflects the urgent need to create jobs. Therefore, the author conducted this research with the aim of addressing the problem of high unemployment rates through a centralized platform that offers job search features and vacancies based on the nearest location for job seekers and providers in the entertainment field, which can be accessed anytime and anywhere. The result of this research is an android application that can facilitate and assist in finding or providing jobs. Through this research the author can contribute to the growth of the entertainment industry in Indonesia, creating new income opportunities for individuals with skills that are usually performed on-site such as singers, magicians, comedians, models, presenters, and other talents in the entertainment sector. This study adopts a qualitative approach, uses the prototype method in the development of the application and applies the Haversine method to calculate the distance between two coordinate points. Thus this study can make a positive contribution in addressing the unemployment problem and increasing job opportunities in the entertainment sector in Indonesia.